Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ma13143152
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Al-Co Alloys at High Temperatures

Abstract: In this work, the high temperature oxidation behavior of Al71Co29 and Al76Co24 alloys (concentration in at.%) is presented. The alloys were prepared by controlled arc-melting of Co and Al granules in high purity argon. The as-solidified alloys were found to consist of several different phases, including structurally complex m-Al13Co4 and Z-Al3Co phases. The high temperature oxidation behavior of the alloys was studied by simultaneous thermal analysis in flowing synthetic air at 773–1173 K. A protective Al2O3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 97 publications
0
19
0
Order By: Relevance
“…[46,47] (Reprinted with permission from [46]. Copyright 2022, Springer Nature), (b) Revisited Al-Co equilibrium phase diagram [43,45,48]).…”
Section: Al-co Phase Constitutionmentioning
confidence: 99%
“…[46,47] (Reprinted with permission from [46]. Copyright 2022, Springer Nature), (b) Revisited Al-Co equilibrium phase diagram [43,45,48]).…”
Section: Al-co Phase Constitutionmentioning
confidence: 99%
“…The data are presented as the composition of the formed oxide film becomes more complex. Šulhánek P. et al [ 73 ] were found that for the formation of a protective film consisting only of Al 2 O 3 , the required concentration of aluminum in the alloy must be more than 20 at. %.…”
Section: Heas Oxidation Productsmentioning
confidence: 99%
“…A high temperature oxidation of several Albased CMAs was also studied [40][41][42]. The presence of high Al concentration improves the corrosion resistance of SCIPs [43,44]. Despite their practical potential, however, the corrosion behavior of Al-TM SCIPs has not been systematically reviewed yet.…”
Section: Quasiperiodicitymentioning
confidence: 99%